Social Security Allowances to Single Women: A Case Study - Kharel, Suman; Parajuli, Chandra; Pradhan, Prajwal Man (Journal of Productive Discourse, 2024)
This paper assesses the impacts of social security allowances provided by the Government of Nepal to single women and the various associated aspects. This study was based on the socio[1]economic status of single women, the nature of tasks performed, and the perception of society and family towards them, which were observed and studied in Phedikhola Rural Municipality, Syangja, using descriptive research methods and related tools such as semi-structured questionnaires, key informant interviews, and observations. Similarly, accessible relevant published or unpublished materials, existing legal provisions, and information available via online means were also referred to as secondary sources. A higher percentage of single women took part in decision[1]making in household non-financial affairs, but involvement in financial affairs was relatively less. Most of them were occasionally invited to social functions and were relatively more trusted by society. The study concluded that the social security allowance can be an important step in uplifting the socio-economic condition of single women. However, the allowance amount needs to be increased to help single women be more independent, and it is also crucial to ensure that the allowances are received by single women and that the expenses are at her discretion.